2019
DOI: 10.2217/cer-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month healthcare utilization and expenditures in Medicare fee-for-service patients with clinically significant mitral regurgitation

Abstract: Aim: This study sought to quantify the healthcare burden of Medicare patients with clinically significant mitral regurgitation (sMR). Materials & methods: Proxy definitions were used for sMR, including MR surgery, atrial fibrillation, pulmonary hypertension or >2 echocardiograms. Results: In this study, 11,173 patients had significant degenerative MR (sDMR); 25,402 had significant functional MR (sFMR); and 12,232 had significant uncharacterized MR (sUMR). Patients with sFMR (18,880) were more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
3
3
Order By: Relevance
“…For patients with sMR, other studies have reported that those with sFMR often have more comorbidities than the other cohorts, which may be associated with higher medical care costs. However, these results were in contrast to ours [ 12 ], which showed that, although the sFMR cohort showed a high prevalence of comorbidities, its healthcare utilization and annual expenditure were actually lower than those of the sDMR cohort. Severe MR can cause HF or heart rhythm problems [ 3 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…For patients with sMR, other studies have reported that those with sFMR often have more comorbidities than the other cohorts, which may be associated with higher medical care costs. However, these results were in contrast to ours [ 12 ], which showed that, although the sFMR cohort showed a high prevalence of comorbidities, its healthcare utilization and annual expenditure were actually lower than those of the sDMR cohort. Severe MR can cause HF or heart rhythm problems [ 3 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This may be the reason why the annual expenditure in the sDMR cohort in this study was eight times higher than that in the DMR cohort and even higher than that in the sFMR cohort. The frequency of casualty visits and hospitalizations and the LOS in this study were significantly higher than those in other studies [12,13]. These results may be due to the character of healthcare in Taiwan-the National Health Insurance scheme and low cost give patients easy access to medical care [16].…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations